Social Dynamics and Its Influences on Islamic Education Policy in the Secular Netherlands - Ningsih, Wirda; Helmiati, Helmiati (IAIN KENDARI, 2025)
This article aims to explore and analyze the secular Dutch government’s stance on Islamic education and its influence on the broader Islamic religious education system in the Netherlands. This qualitative study relies on data collected from library resources, including some regulations, books, and journal articles. Employing interpretative analysis, this study found that the government’s policy on Islamic religious education in the Netherlands has been significantly shaped by its historical and socio-cultural contexts. The growth of Islamic education in the Netherlands is coinciding with the rise in the number of Muslim immigrants. The greater the number of Muslim immigrants in the Netherlands, the stronger the government's attention to Islamic religious education. In the 20th century, the Netherlands showed a significant increase in the number of Muslim immigrants, which influenced the stronger government support for Muslim education. As a result, the Islamic education system has progressed in various aspects and gained its authority. This study implies that social dynamics have significant influences on Islamic education, even in a secular state like the Netherlands